Educational Packages on Breastfeeding Increase Behavior and Self-Efficacy of Mothers - Maizuputri, Stefi; Mutmainnah, Muthia; Meinarisa (Jurnal Berita Ilmu Keperawatan, 2024)
As a specific breastfeeding practice, the proportion of exclusive breastfeeding in Indonesia remains below the intended indicator. Education about breastfeeding techniques aims to increase success in providing exclusive breastfeeding by increasing mothers' knowledge and skills in breastfeeding their babies. The goal of this study is to find out how the Jambi City Health Center's breastfeeding education program affects moms' confidence and nursing behavior. Mothers who had just given birth or were nursing their babies participated in this study. Using a control group and a quasi-experimental design with pre- and post-test measures, the study used a quantitative methodology. Using accidental sampling, 25 respondents from the treatment and control groups made up the sample. The variables measured are maternal behavior and self-efficacy. The measuring instruments used were the breastfeeding action instrument and the BSES-FS. The treatment group's behavioral results produced a p-value of 0.001 (<0.05) according to statistical analysis using the Wilcoxon test, while the control group's p-value was 0.629 (>0.05). In a similar vein, the treatment group's p-value for self-efficacy outcomes was 0.001 (<0.05), but the control group's was 0.122 (>0.05). These findings imply that nursing moms' behavior and self-efficacy are significantly impacted by teaching packages on breastfeeding procedures delivered by video and booklet medium. In particular, compared to the control group that did not get the intervention, the treatment group, who did receive the intervention, exhibited improved behavior and greater levels of self-efficacy.